2014
DOI: 10.1016/j.compmedimag.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Normalized gradient fields for nonlinear motion correction of DCE-MRI time series

Abstract: Dynamic MR image recordings (DCE-MRI) of moving organs using bolus injections create two different types of dynamics in the images: (i) spatial motion artifacts due to patient movements, breathing and physiological pulsations that we want to counteract and (ii) signal intensity changes during contrast agent wash-in and wash-out that we want to preserve. Proper image registration is needed to counteract the motion artifacts and for a reliable assessment of physiological parameters. In this work we present a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In simulated results, matching using HOG descriptors performed well, but tests on real images lead to coarse and inaccurate depth maps. Using normalized gradients to compute global registration for medical images was proposed by Haber and Modersitzki [57] and extended Rühaak et al [58] and by Hodneland et al [59] among others. These works are intended to align medical images (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…In simulated results, matching using HOG descriptors performed well, but tests on real images lead to coarse and inaccurate depth maps. Using normalized gradients to compute global registration for medical images was proposed by Haber and Modersitzki [57] and extended Rühaak et al [58] and by Hodneland et al [59] among others. These works are intended to align medical images (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…This phenomenon favours the use of a gradient dependent cost functional for registration. In recent work [14], [24] it was shown that normalized gradient fields (NGF) was a viable alternative to MI for the registration of DCE-MRI images. In this work, we therefore incorporate a version of NGF [21], [35] as data term for the registration task.…”
Section: ) Registrationmentioning
confidence: 99%
“…The spatial derivative of a function f was approximated either by central (D c ), forward (D + ) or backward (D − ) differences. The Euler-Lagrange equations to solve are given by (24). Note that b(u, φ) is not depending on u and φ through a differential operator, and is therefore applied on the right hand side.…”
Section: Numerical Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several methods have been proposed to compensate for motion in DCE-MR series of the abdomen. Some approaches have used pairwise registration methods with mutual information (MI) as metric, where the individual images are registered one by one to a reference image (Rueckert et al [1999], Rohlfing et al [2003], Wells et al [1996], Hodneland et al [2014], Zöllner et al [2009]). These methods generally do not achieve the temporal smoothness needed for visual assessment, because of bias towards the choice of reference (Huizinga et al [2016], Metz et al [2011]).…”
Section: Introductionmentioning
confidence: 99%